Sexually transmitted infections: old foes on the rise - Carmona-Gutierrez, Didac (Microb Cell, 2016)
Sexually transmitted infections (STIs) are commonly spread via sexual contact. It is estimated that one million STIs are acquired every day worldwide. Besides their impact on sexual, reproductive and neonatal health, they can cause disastrous and life-threatening complications if left untreated. In addition to this personal burden, STIs also represent a socioeconomic problem, deriving in treatment costs of tremendous proportions. Despite a substantial progress in diagnosis, treatment and prevention, the incidence of many common STIs is increasing, and STIs continue to represent a global public health problem and a major cause for morbidity and mortality. With this Special Issue, Microbial Cell provides an in-depth overview of the eight major STIs, covering all relevant features of each infection.